Energy and exergy analysis of entrained bed gasifier/GT/Kalina cycle model for CO2 co-gasification of waste tyre and biochar - ÖZVEREN, UĞUR (My University, 2023)
© 2022 Elsevier LtdIntegrated gasification combined cycle (IGCC) is a power generation technology that partially oxidizes solid feedstocks to produce syngas, drives high-efficiency gas turbines (GT), recovers waste heat and uses it to generate electricity, etc. In this study, a new IGCC model for an entrained bed gasifier/GT/Kalina cycle for CO2 co-gasification was developed for the first time using Aspen HYSYS, and an energy and exergy analysis of this model was performed to provide decision makers with a comprehensive overview of whether the energy conversion system is designed to be sustainable from a variety of perspectives. The newly proposed integrated system was used to study the CO2/air gasification process of the biochar/waste tyre blend. Although entrained bed gasifiers have been modelled using different software and different fuels, no study on the Kalina cycle integrated biochar/waste tyre co-gasification process using Aspen HYSYS has not been reported yet. In addition, most parametric studies on integrated Kalina combined cycles focus on the influence of the Kalina cycle or a few operating factors. However, in this study, the effects of a variety of gasification process operating conditions on the performance of the combined cycle are considered. The equivalence ratio (ER) for a high-efficiency integrated system ranged from 0.23 to 0.25, and the CO2 content in the gasifying agent was in the range of 5–7%. While increasing the waste tyre content in the feedstock enhances H2 production, operating the entrained bed gasifier at relatively low temperature is more efficient. Increasing the ammonia content in the working fluid also improves efficiency, and the inlet pressure of the Kalina turbine should be maintained at 28 bar to maximize performance. While the integration of the GT enables significant power generation, optimizing the operating conditions of the gasifier, which has the highest exergy dissipation, is critical to the performance of the integrated system.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Kimya Mühendisliği ve Teknolojisi; Kimya; Biyokimya; Biyoinorganik Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Chemical Engineering and Technology; Chemistry; Biochemistry; Bioinorganic Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; MÜHENDİSLİK, KİMYASAL; ENERJİ VE YAKITLAR; KİMYA, ORGANİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; CHEMISTRY; ENGINEERING, CHEMICAL; ENERGY & FUELS; CHEMISTRY, ORGANIC; Genel Kimya Mühendisliği; Fizik Bilimleri; Yakıt Teknolojisi; Enerji Mühendisliği ve Güç Teknolojisi; Organik Kimya; General Chemical Engineering; Physical Sciences; Fuel Technology; Energy Engineering and Power Technology; Organic Chemistry; CO2 Co-Gasification; Kalina Cycle; IGCC; Waste Tyre; Aspen HYSYS